2014
DOI: 10.5835/jecm.omu.31.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum vitamin D levels in elderly patients with subclinical hypothyroidism

Abstract: Article HistoryReceived 12 / 05 / 2014 Accepted 07 / 06 / 2014Increasing numbers of researches have indicated the relationship between serum vitamin D level and several autoimmune diseases, because it has important roles in immune regulation. However, the role of vitamin D in the etiopathogenesis of these diseases is not well understood. Similarly, the detailed mechanism of vitamin D action on thyroid hormone metabolism and autoimmune thyroid diseases is still poorly understood. It was recently reported that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Among these, 9 studies were from Turkey [ 26 , 34 , 36 , 37 , 39 , 42 , 43 , 48 , 49 ], 3 each from Saudi Arabia [ 17 , 32 , 35 ], Poland [ 38 , 52 , 59 ], China [ 27 , 28 , 51 ] and Korea [ 54 , 55 , 58 ], 2 each from Egypt [ 50 , 60 ] and Italy [ 40 , 57 ] and one each from Belgium [ 25 ], Canada [ 33 ], Brazil [ 44 ], Japan [ 47 ], India [ 45 ], Sweden [ 46 ], Thailand [ 53 ], Greece, United States [ 56 ], and Ukraine [ 31 ]. Among the 35 studies, 29 recruited both genders [ 25 , 27 32 , 34 41 , 43 46 , 48 56 , 58 ], 4 only women [ 17 , 42 , 47 , 57 ], and 2 studies did not report the gender [ 26 , 33 ]. Eighteen studies mentioned BMI [ 27 , 28 , 30 , 31 , 33 , 35 , 36 , 40 , 45 , 47 , 50 53 , 55 58 ] and 26 studies pointed to the time of ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among these, 9 studies were from Turkey [ 26 , 34 , 36 , 37 , 39 , 42 , 43 , 48 , 49 ], 3 each from Saudi Arabia [ 17 , 32 , 35 ], Poland [ 38 , 52 , 59 ], China [ 27 , 28 , 51 ] and Korea [ 54 , 55 , 58 ], 2 each from Egypt [ 50 , 60 ] and Italy [ 40 , 57 ] and one each from Belgium [ 25 ], Canada [ 33 ], Brazil [ 44 ], Japan [ 47 ], India [ 45 ], Sweden [ 46 ], Thailand [ 53 ], Greece, United States [ 56 ], and Ukraine [ 31 ]. Among the 35 studies, 29 recruited both genders [ 25 , 27 32 , 34 41 , 43 46 , 48 56 , 58 ], 4 only women [ 17 , 42 , 47 , 57 ], and 2 studies did not report the gender [ 26 , 33 ]. Eighteen studies mentioned BMI [ 27 , 28 , 30 , 31 , 33 , 35 , 36 , 40 , 45 , 47 , 50 53 , 55 58 ] and 26 studies pointed to the time of ...…”
Section: Resultsmentioning
confidence: 99%
“…Pursuant to subgroup analysis, vitamin D and hypothyroidism were associated only among studies recruiting both genders (WMD − 15.43 ng/dl; 95% CI, − 29.49 to − 1.37) and studies that included the non-Asian population (WMD − 14.31 ng/dl; 95% CI, − 26.53 to − 2.10) (Table 2 ). Keeping out a number of studies including Ucar et al [ 34 ] (WMD − 11.33 ng/dl; 95% CI, − 22.76 to 0.08), Mackawy et al [ 32 ] (WMD − 11.40 ng/dl; 95% CI, − 22.92 to 0.10), Mirhosseini et al [ 33 ] (WMD − 14.41 ng/dl; 95% CI, − 29.01 to 0.18), Fawzy et al (a) [ 29 ] (WMD − 11.98 ng/dl; 95% CI, − 24.84 to 0.86) and Fawzy et al (b) [ 29 ] (WMD − 11.10 ng/dl; 95% CI, − 22.33 to 0.13) modified the overall effect. Due to evidence of publication bias (Begg’s test: P = 0.835, Egger’s test: P = 0.006), possible un-detected studies were tracked by trim and fill analysis, but this method could not add any dataset to our included ones.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mackawy et al measured serum 25(OH)D levels in 30 hypothyroid patients and 30 healthy participants, discovering that hypothyroid patients had hypovitaminosis D with hypocalcemia, which was significantly associated with the degree and severity of hypothyroidism [ 94 ]. In a retrospective study done in Turkey, Ucar et al demonstrated that serum 25(OH)D levels in elderly patients with subclinical hypothyroidism were lower than in healthy controls [ 95 ]. Aljohani et al, in a cross-sectional case-control study, found an inverse association between vitamin D status and FT3 [ 96 ].…”
Section: Reviewmentioning
confidence: 99%